The Role of Soluble Organic Matter in Shale Oil “Sweet Spots” Prediction: An Investigation of Shale With Different Lithofacies in the Dongying Sag - He, Jinyi; Cai, Jingong; Zhu, Xiaojun; Song, Mingshui; Liu, Huimin; Wang, Xuejun; Zeng, Xiang (Frontiers in Earth Science, 2021)
Lithofacies are the fundamental geological units for shale oil and gas exploration and development, and soluble organic matter (SOM) is most similar to crude oil in composition. Both aspects attract our attention in the interpretation of SOM in different lithofacies, which can provide direct evidence to predict shale oil “sweet spots”. Here, twenty-five shale samples were collected from the Eocene Shahejie Formation in the Dongying Sag and were subjected to X-ray diffraction, Rock-Eval pyrolysis, and SOM characterization. Comparison of the SOM contents in shales with different lithofacies revealed remarkable differences: 1) The contents of SOM, saturates and total hydrocarbons (THC) showed the order of detrital massive mudstone < homogenous massive mudstone < wide laminated shale < discontinuous laminated shale < fine laminated shale < gypsum-bearing mudstone, and the SOM content was controlled by lithofacies through differences in both OM and minerals. 2) The SOM in detrital and homogenous massive mudstones was mainly composed of saturates and resins. Saturates were the main component in wide and fine laminated shales. The SOM in discontinuous laminated shale was mainly composed of saturates and aromatics. The SOM in gypsum-bearing mudstone was mainly composed of saturates, and the percentage of asphaltenes was quite high. Based on the evaluation parameters of high-quality lithofacies in terms of abundance (i.e., SOM, THC or saturate contents) and quality (i.e., quality index and asphaltene percentage), the fine, wide and discontinuous laminated shales were regarded as relatively favorable lithofacies. Based on the lithofacies combination, the fine, wide and discontinuous laminated shales in Es3x and Es4ss (upper section of Es4s) in the Dongying Sag were interpreted as “sweet spots” for shale oil exploration and development. Thus, it is of great significance to study the characteristics of SOM in shale with different lithofacies for shale oil exploration and development.